Multiculturalismo e direitos de grupos segundo a concepção de Kymilicka - Lima, Ana Paula Brito Abreu de (2012)
Kymlicka s multiculturalism, that he calls Liberal Theory of Minority Rrights, results from his involvement in a new discussion of problems which was originated by the cultural diversity, that characterizes the majority of modern societies, composed by a plurarity of ethinic groups , religious groups etc, which sometimes have a language, customs or way of thinking that are really different from those of the other groups . Such differences tend to generate severe tensions and social antagonisms that, as time goes by, turn even more evident that minority rights cannot be absorbed by human rights. To solve these questions in a fair manner, accord to Kymlicka, it s necessary to supplement the traditional principles of human rights with a theory of minority rights. Based on the study of Will Kymlicka s Multiculturalism, which focuses groups and minorities rights, this work intends to bring critical elements to Brazilian Constitutionalism, specially in what is related to the dignity of the human person principle, which identifies a space of moral integrity to be assured to every person, because of her existence in the world and represents the overcoming of intolerance, discrimination, social exclusion, violence, incapacity of accepting the other, the different, in the plenitude of his freedom of being, think and create.